Microfluidics and molecular diagnostics in renal cell carcinoma: advances, challenges, and future directions - Abu-Dawas, Sadeq B.; Alwadi, Aiman Y.; Farahat, Yara H.; Abu-Dawas, Reema B.; Quraiba, Lama N.; Abu-Omar, Reem A.; AlKattan, Khaled; Khan, Mohammed Imran; Yaqinuddin, Ahmed (Frontiers in Oncology, 2025)
RCC represents the predominant form of kidney cancer, with rising global incidence and notable mortality despite advancements in diagnosis and treatment. Traditional imaging and histopathological techniques, while foundational, face limitations in early detection, subtype differentiation, and treatment personalization. This review comprehensively explores RCC’s clinical and pathological landscape, then transitions to focus on recent innovations in microfluidics and molecular diagnostics that are reshaping kidney cancer management. Microfluidic platforms facilitate efficient, minimally invasive analysis of biomarkers such as CTCs, ctDNA, and exosomes, enabling real-time disease monitoring and drug response assessment. Biomolecular technologies—including single-cell sequencing, spatial transcriptomics, and next-generation sequencing—offer deeper insights into tumor heterogeneity and therapeutic resistance. The integration of multi-omics data and emerging platforms like kidney cancer-on-a-chip highlight the promise of precision medicine. Challenges in clinical translation, including assay standardization and regulatory hurdles, are also addressed. Together, these developments underscore a paradigm shift toward individualized, biomarker-driven care in RCC.